Dual growth factor loaded nonmulberry silk fibroin/carbon nanofiber composite 3D scaffolds for in vitro and in vivo bone regeneration. (August 2017) - Naskar, Deboki; Ghosh, Ananta K.; Mandal, Mahitosh; Das, Piyali; Nandi, Samit K.; Kundu, Subhas C.
Abstract: In recent years the potential application of nanocomposite biomaterials in tissue engineering field is gaining importance because of the combined features of all the individual components. A bottom-up approach is acquired in this study to recreate the bone microenvironment. The regenerated silk protein fibroin obtained from nonmulberry tropical tasar Antheraea mylitta species is reinforced with functionalized carbon nano fiber (CNF) and the composite sponges are fabricated using facile green aqueous based method. Biophysical investigations show that the matrices are porous and simultaneously bioactive when incubated in simulated body fluid. The reinforcement of CNF influences the mechanical property of the matrices by increasing the compressive modulus up to 46.54 MPa (∼4.3 times of the control fibroin sponge) in hydrated state, which is higher than the minimum required human trabecular bone modulus (10 MPa). The composite matrices are found to be non-hemolytic as well as cytocompatible. The growth factors (BMP-2 and TGF-β1) loaded composites show sustained release kinetics and an early attachment, growth, proliferation, and osteogenic differentiation of the osteoblasts and mesenchymal stem cells. The matrices are immunocompatible as evidenced by minimal release of pro-inflammatory cytokines both in vitro and in vivo . In order to support the in vitro study, in vivo analysis of new bone formation within the implants is performed through radiological, μ-CT, fluorochrome labeling and histological analysis, which show statistically better bone formation on growth factor loaded composite scaffolds. The study clearly shows the potential attributes of these composite matrices as an extra cellular matrix for supporting successful osseointegration process.